Age, gender, and BMI in presentation of primary hyperparathyroidism: a single-center experience - Katarina Mlekus Kozamernik; Gaj Vidmar; Mojca Jensterle Sever; Luka Lezaic; Marko Hocevar; Soncka Jazbinsek; Katarina Remec; Andrej Janez; Tomaz Kocjan (Endokrynologia Polska)
BACKGROUND: Primary hyperparathyroidism (PHPT) is a relatively common disease with considerable heterogeneity. We aimed to assess the impact of age, gender, and body mass index (BMI) on the presentation of PHPT. MATERIAL AND METHODS: We retrospectively analyzed the baseline biochemical status, symptoms, renal manifestations, and bone mineral density (BMD) of patients diagnosed with PHPT at the national tertiary endocrine referral clinic from January 2004 to December 2016. RESULTS: We included 415 patients (333 women [41 premenopausal, 292 postmenopausal] and 82 men) with PHPT, aged 64 years on average [standard deviation (SD)13, range 19–89 years], with an average BMI of 28.4 (SD 6.0, range 11.2–51.1 kg/m²). Older age was statisticallysignificantly associated with milder biochemical presentation — lower total and corrected calcium (standardized regression coefficient β = –0.17, p < 0.001 and β = –0.12, p = 0.018). In comparison with premenopausal women, postmenopausal women [estimated odds ratio (OR) = 8.6, 95% confidence interval (CI): 3.9–20.8; p < 0.001] and men (OR = 5.9, 95% CI: 2.5–15.6; p < 0.001) were more likely to suffer from skeletal manifestations of PHPT. Renal manifestations were less likely among postmenopausal than premenopausal women (OR = 0.4, 95% CI: 0.2–0.8; p = 0.014). BMI was negatively associated with skeletal and renal manifestations (OR = 0.94 per unit change, p = 0.002) and symptomatic presentation (OR = 0.96 per unit change, p = 0.012). CONCLUSION: Older patients with PHPT presented with a biochemically less florid disease. Postmenopausal women and men with PHPT were more likely to suffer from skeletal manifestations of PHPT than premenopausal women. Patients with higher BMI had fewer skeletal and renal manifestations of PHPT and were less likely to be symptomatic.